ANALISIS KEMAMPUAN NUMERASI SISWA BERKESADARAN METAKOGNISI TINGGI DALAM MENYELESAIKAN SOAL GEOMETRI - Ida Rosita; Syamsuri Syamsuri; Hepsi Nindiasari; Sukirwan Sukirwan (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2021)
This study aims to analyze the metacognitive skills of students with reflective-impulsive cognitive style in solving geometry problems. This type of research uses descriptive qualitative methods. Data collection techniques used instruments in the form of a Metacognitive Awareness Inventory (MAI) questionnaire, a written test in the form of geometry questions in the form of a validated essay and interviews were conducted to obtain in-depth data. Subjects were selected using a purposive sampling technique based on the results of the MAI questionnaire filling test. The results showed that students who have high metacognitive awareness are able to perform the stages of metacognition skills in problem solving and tend to have a reflective-impulsive cognitive style. Students with reflective cognitive style are able to and through all stages of metacognitive skill processes in problem solving from the planning, monitoring and evaluating stages more thoroughly and in detail, requiring a long time to solve problems but the results obtained tend to be true or accurate and can perform and regulate cognitive activities and be aware of the metacognitive activities carried out. Meanwhile, students with an impulsive cognitive style perform the problem-solving stages of the planning, monitoring and evaluating stages, which seem rushed and tend to be less thorough. Students who have an impulsive cognitive style can perform the stages of metacognitive skills in problem solving but have not been able to manage all cognitive activities and are not aware of the metacognitive activities carried out. Keywords: reflective-impulsive cognitive style, metacognitive awareness, problem solving